Адаптивні алгоритми розв’язування систем інтегральних рівнянь - Федорчук, В.А.; Тихоход, В.А. (Моделювання та інформаційні технології, 2009)
The algorithm of the decision of systems of the linear integrated equations by a method of collocations with use of an adaptive choice of a step of integration is considered.